If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2 = g + -1o Solving -2 = g + -1o Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-1g' to each side of the equation. -2 + -1g = g + -1g + -1o Combine like terms: g + -1g = 0 -2 + -1g = 0 + -1o -2 + -1g = -1o Add '2' to each side of the equation. -2 + 2 + -1g = 2 + -1o Combine like terms: -2 + 2 = 0 0 + -1g = 2 + -1o -1g = 2 + -1o Divide each side by '-1'. g = -2 + o Simplifying g = -2 + o
| -108=-12(10v-1)-6(5v-5) | | -110=2(-6x-7) | | 6x^4-9x^2+3= | | 20x+25y=500 | | 65+18*8= | | -8(6v+4)=208 | | 28x^2-3x-4=0 | | 146=2-8(6k-6) | | 5x+60y= | | -x+-11=-63 | | 72x^3-228x^2+140x= | | 88=-8(n-3) | | 2s+3s-14.4=6.8 | | 22(4x)=30 | | 8(w-8)=7(7+w) | | y^2-8y-10=0 | | x+(x+3)+(x-5)=78 | | 18(-2)-(-6)+5= | | 3x^3-7x^2+x= | | w^2-5w+4= | | 9=6-5d | | -2y-3+8=8-5y-12 | | 24x^4+18x^3-27x^2= | | (3n+22)+(2n+18)=180 | | -5(3-7a)=-85 | | 100-80+-4= | | 13a+1=17a+5 | | 15-5x=6-2x | | 6p-5p+5=-8-2(p+12) | | 10-3x-6-3x=7 | | 6-8(5+5p)=-194 | | 13+6p-9-4p-p=49 |